PENINGKATAN PENGEMBANGAN KARIR MELALUI KOMPETENSI KERJA DAN PRESTASI KERJA DI DINAS PARIWISATA PROVINSI BANTEN - Sukmawati, Sukmawati; Khaeruman, Khaeruman; Abduh, Edi Muhammad (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
Career development is an important aspect in improving the quality and effectiveness of employee work. At the Banten Province Tourism Office, work competency and work performance are identified as the main factors influencing career development. This research aims to examine the relationship between competency and work performance and career development. This research aims to examine increasing career development through work competency and work performance at the Banten Province Tourism Office. The method used is a survey with a descriptive quantitative approach. The research population was 103 respondents, using Simple Random Sampling sampling techniques, resulting in 34 respondents as samples. Data was collected using a questionnaire and analyzed using multiple regression techniques. The research results show that the Work Competency variable (X1) has a tcount value of -2.114 and a significance of 0.043, which means tcount > ttable (-2.114 > 0.682486). The Job Performance variable (X2) has a tcount value of 6.641 and a significance <0.001, which also shows tcount > ttable (6.641 > 0.682486). Hypothesis testing using the F test produces an F value of 16.384 with a significance of <0.001. These results indicate that work competency and work performance significantly influence career development at the Banten Province Tourism Office